Oxidative Stress and Inflammation-Related mRNAs Are Elevated in Serum of a Finnish Wet AMD Cohort - Liukkonen, Mikko; Heloterä, Hanna; Siintamo, Leea; Ghimire, Bishwa; Mattila, Pirkko; Kivinen, Niko; Kostanek, Joanna; Watala, Cezary; Hytti, Maria; Hyttinen, Juha; Koskela, Ali; Blasiak, Janusz; et al. (Association for Research in Vision and Ophthalmology (ARVO), 2025)
Purpose: Localized diseases can be affected by and affect the systemic environment via blood circulation. In this study, we explored the differences in circulating serum mRNAs between patients with wet AMD (wAMD) and controls.
Methods: Blood samples were obtained from 60 Finnish patients with wAMD and 64 controls. After serum preparation and RNA sequencing, the count data was examined for differentially expressed genes (DEGs) and further checked for enriched molecular pathways and ontology terms as well as links to clinical data.
Results: We found many DEGs and some enriched pathways, including the inflammation and cell survival-associated pathway tumour necrosis factor alpha (TNF-α) signaling via nuclear factor kappa–light-chain-enhancer of activated B cells (NF-κB). The related DEGs were oxidized low-density lipoprotein receptor 1 (OLR1), salt inducible kinase 1 (SIK1), and coagulation factor III (F3). DEGs from degradative macular and retinal processes were also examined, many of which were also related to cardiovascular disease and maintenance. Additionally, DEG counts were inspected in relation to clinical and anti-VEGF treatment parameters, and glutamine amidotransferase-like class 1 domain-containing 3A (GATD3A) levels were found to be significantly lower in patients with wAMD treated with anti-VEGF.
Conclusions: Differentially expressed systemic mRNAs that are linked to mitochondrial function, oxidative stress, and inflammation may have a role in the pathology of wAMD. Our observations provide new data for the understanding of the progression of wAMD.